Comparative study of overweight and obesity among government and private school children in Guntur - Gujjarlapudi, Chaitanya; Dulipala, Phanindra; Rao, D. J.; KL, Tejaswini (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Various studies conducted in India indicate a rising trend in the prevalence of overweight and obesity in children. This alarming rise in childhood obesity is often attributed to increased intake of high calorie foods, coupled with decreased physical activity. Obesity is also a major risk factor for Non Communicable diseases like Diabetes Mellitus, Cardiovascular diseases and Cancer. The aim of the study was to find out the magnitude and risk factors for overweight and obesity among school children attending government and private schools. Methods: A school based cross sectional study was conducted in three government and three private schools among children enrolled in 6th to 10th standard. Information regarding consumption of fruits / week, junk food, intake of carbonated drinks, and time spent on viewing of television and physical activity was collected by using a predesigned and pretested questionnaire. Body Mass Index (BMI) was calculated by using the formula, BMI= Weight in kilograms / (Height in meter)2 . Overweight and obesity were categorized by ELIZ Health Pathway for Adolescents. Results: The mean age of study participants was 13.2 ± 1.19 years. Information was collected from a total of 1043 school children studying 6th to 10th class of which 495 (47.45%) and 548 (52.54%) were enrolled in government and private schools respectively. Among government school children the consumption of carbonated drinks (55.75%) and junk foods (80.6%) was significantly higher when compared to private school children (36.49% and 68.06% respectively). The proportion of overweight and obesity was 4% and 1.8% in government and 16.2% and 10% in private schools respectively. Conclusion: Several risk factors are prevalent among government and private school children. Early detection of the risk factors and timely interventions are needed to prevent their progression to overweight and obesity in future. Simple strategies involving health and nutrition education and physical activity could go a long way in preventing overweight and obesity and their consequences.